Developing Android-Based Interactive Learning Media Assisted by Smart Apps Creator on Atomic Structure Material - Faisal, Faisal; Susilowati, Susilowati; Rumihin, Tamar; Murtihapsari, Murtihapsari (Jurnal Tadris Kimiya, 2025)
The integration of digital technology in chemistry education necessitates the development of innovative learning media to facilitate students’ comprehension of abstract and complex concepts, such as atomic structure. This study aimed to develop and validate an Android-based interactive learning medium and to examine its practicality for chemistry learning. A research and development (R&D) methodology was employed, utilizing the 4-D model comprising define, design, develop, and disseminate stages. During the define stage, students’ learning needs and difficulties were identified through classroom observations, interviews, and needs analysis questionnaires. The design stage involved the formulation of learning objectives, content organization, and the development of a media prototype. In the develop stage, the learning media was evaluated using validation instruments completed by experts in chemistry content, instructional media, and learning design. The disseminate stage focused on assessing practicality through student response questionnaires. The results revealed that the developed learning media achieved high validity, with mean expert validation scores of 3.86 for content, 3.80 for media, and 3.85 for design, resulting in an overall mean score of 3.83, categorized as very valid. Furthermore, student responses indicated a high level of practicality, with an average score of 3.55, classified as very positive. These findings suggest that the Android-based interactive learning media is feasible and practical for supporting students’ understanding of atomic structure and has strong potential for implementation in chemistry learning contexts.